Costi sanitari di un programma vaccinale: analisi di minimizzazione dei costi - Colombo, G. L.; Muzio, A.; Giordani, R. (Farmeconomia. Health economics and therapeutic pathways, 2003)
The global cost of a vaccination program is made up by many more cost components than the acquisition expense, although the former is the first cost usually taken into consideration when comparing two or more alternatives. The present article analyses the economical impact consequent to the use of two different hexavalent vaccine formulations (Hexavac, liquid ready for injection, and Infanrix Hexa, dry, to be re-hydrated) available on the Italian market for the mandatory vaccination of newborns during their first year of life. The cost minimization analysis was conducted considering only differential costs, i.e. those costs than can differ with the use of one of the two products, and not those common to the two competing products, such as acquisition cost (33 euro in average for both), the costs for the organization, the call of the infants to be vaccinated, etc.. The differences among the considered alternatives detected by this study regard the work for the preparation and administration of the vaccines, the quantity of special waste they produce and the incidence of serious febrile reactions leading to pharmacological treatment and physician consultation (body temperature > 40°C). The liquid formulation resulted more convenient in terms of cost for nurse work (0,63 euro saved per patient), waste disposal, and adverse reactions management. The robustness of these results was confirmed by sensitivity analysis and an estimate of the global saving for the Italian health system associated with the universal utilization of the liquid formulation is furnished.